The effects of energy drinks, drugs and hormones that taken by the bodybuilding sportsmen on the some liver and kidneys functions in Kirkuk city - Fidan Fikrat. Ahmed (Tikrit Journal of Pure Science)
The present study included one hundred ten volunteers (bodybuilding sportsmen; Ninety sportsmen took stimulants and twenty without stimulants). Then, volunteers distributed to four groups according to the types of stimulant. The first group was control group without stimulants. The second group sportsmen who used energy drinks (Red bull and Power Horse). The third group sportsmen who used drugs (max miz (100mg), XXL protein (100mg)، sirios mass (200mg). The fourth group sportsmen who used hormones(testosterone، insulin، growth hormone، nandrolone، primobolan and stanazol).